Automotive Door Design (Global Journals of Research in Engineering, 2012)
This research papers describes the drawbacks of existing automotive door structure and suggest design changes to overcome the present drawbacks. This research paper details out the analysis of the existing structure and identifies the drawbacks and explains the process of door system design. Changes required can be found out with correct method as explained in this paper. Validation of the design parameters is of vital importance so the way by which validation of newly designed or modified parts can be done is briefly explained in this paper. Designer from an automobile engineer faces so many different problems during their work. Some of the major problems in automobile door are taken as problem for this research paper and those problems like high weight, high cost, excessive reinforcements, and water leakage. At first theoretically study of the existing system is done. After that deciding the key areas of modification is the flow of this paper. After finding the modification areas we tried some parameters for calculation. On the basis of calculations the design of new parts are finalized. Then 3D models are prepared in CATIA V5, which are used for analysis purpose. Finally on the basis of analysis results actual metal parts are developed in the proto shop and fitment trials are taken on the vehicle. Once the fitment trial is completed actual testing is done on the vehicle. Comparing those results with the old results the improvement is suggested, during this study some specific parameters are chosen for observation and improvement. On the basis of these results final design is frizzed.
Keywords: ULSAB Concept; Problems in TWB technology; new inner panel for hardpad; water leakage issue